Integrative analysis of single nucleotide polymorphism of PDE7B (rs2327669) with biopsychosocial and biochemical parameters in β-thalassemia major patients in Pakistani Cohort - Faiza Usmani; Muhammad Zohaib Yaseen; Arshi Ali; Mahrukh Nasir; Saifullah (Molecular Biology Reports, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

Synergistic Effects of Biochar with Phosphorus Fertilization on soil Biochemical Properties and Wheat Productivity - Nighet Musa; Khalid Saifullah Khan; Muhammad Azeem; Mah-Noor Azad; Mehnoor Khan; Nabeeha Javed; Tajwar Alam (Journal of Soil Science and Plant Nutrition, 2026)

Foliar application of silicon alleviates adverse effect of drought stress by improving growth, physiological attributes, and antioxidant defense of camelina (Camelina sativa L.) - Bilal Ahmad Shahzad; Ejaz Ahmad Waraich; Muhammad Saleem; Saddam Hussain; Saifullah (Acta Physiologiae Plantarum, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Corrigendum to “global research on the air quality status in response to the electrification of vehicles” [Science of the Total Environment, 795, (2021), 148861] - Yansong Bao; Khalid Mehmood; Saifullah; Muhammad Yaseen; Saad Dahlawi; Muhammad Mohsin Abrar; Shah Fahad (Science of The Total Environment, 2026)

Synthesis of biocompatible novel multi-tailed indole-based resorcinarene for effective delivery of quercetin against multidrug-resistant S. aureus - Khadija Rehman; Tasmina Kanwal; Muhammad Hasnain; Rukesh Maharjan; Wajeeha Muzafar; Komal Rao; Salim Saifullah; Shabana Usman Simjee; Muhammad Raza Shah (Archives of Microbiology, 2026)

Phenol-rich bio-oil synthesis via single and dual metal-oxide/zeolite catalysts in biomass catalytic pyrolysis: Comparison of Y2O3/ZSM-5 and MgO/Y2O3/ZSM-5 - Alien Abi Bianasari; Minh Thang Le; Muhammad Saifullah Abu Bakar; Saepurahman; Dieni Mansur; Fairuzeta Hj Md Ja'afar; Quentin Cheok; Abul Kalam Azad (Biomass and Bioenergy, 2026)

Sustainable materials for electric vehicle batteries: A comprehensive review of progress, challenges, and opportunities - Noor Hafidzah Jabarullah; Muhammad Saifullah Abu Bakar; Teguh Kurniawan; Asep Bayu Dani Nandiyanto; Asim Laeeq Khan; Fatin Amanina Azis; Muhammad Roil Bilad (Next Research, 2025)

Recirculating aquaculture systems: Advances, impacts, and integrated pathways for sustainable growth - Zubair Hashmi; Faizah Metali; Muhamad Amin; Muhammad Saifullah Abu Bakar; Yusuf Wibisono; Wahyunanto Agung Nugroho; Muhammad Roil Bilad (Bioresource Technology Reports, 2025)

Assessing the Diversity of Decapods (Crustacea: Malacostraca) With Environmental DNA ( eDNA ) in Coastal Water of Matang, Perak, Malaysia - Chuan‐Hui Lim; Sze‐Looi Song; Zulqarnain Bin Mohamed; Muhammad Fadhli Mat Sobri; Azmi Marzuki Muda; Saifullah Arifin Jaaman (Marine Ecology, 2025)
Decapods play vital ecological and economic roles, yet their diversity and distribution in the coastal waters of Matang remain poorly understood. Increasing anthropogenic pressures have further impacted their habitats, underscoring the need for improved biodiversity assessments. Conventional monitoring methods are often limited by inconsistencies, invasiveness, low taxonomic resolution, and inefficiency in complex habitats. This study evaluated the effectiveness of environmental DNA (eDNA) metabarcoding to assess decapod diversity in Matang waters. A total of 136 seawater samples were collected from predefined zones between October 2021 and October 2022. DNA was extracted using the CTAB method, and a partial mitochondrial cytochrome c oxidase subunit 1 (COI) gene region was amplified. The amplicons were sequenced using the Illumina MiSeq platform. This approach identified 12 decapod species from six families: Penaeidae (3 species), Lucideridae (1 species), Sergestidae (3 species), Dotillidae (1 species), Pilumnidae (1 species), and Diogenidae (3 species). Dominant species included Acetes japonicus (46%), Acetes indicus (27%), and Diogenes fasciatus (10.9%). Notably, eight species matched records from previous conventional surveys, while four additional taxa: 2 Diogenes spp. ( Diogenes fasciatus , Diogenes rectimanus ), a Dotillidae crab ( Ilyoplax serrata ), and a Pilumnidae crab ( Aniptumnus sp.) were newly detected in the area. These findings indicate that decapod richness in Matang is likely underestimated. In summary, eDNA metabarcoding offers a promising, non‐invasive alternative for biodiversity monitoring in dynamic environments and complements traditional methods. This study establishes a foundation for long‐term decapod monitoring and supports conservation efforts in the Matang region.

Seasonal and interannual variability of Karakoram glacier surface albedo from AVHRR-MODIS data, 1982–2020 - Fuming Xie; Shiyin Liu; Tobias Bolch; Yu Zhu; Yongpeng Gao; Shucheng Tan; Muhammad Mannan Afzal; Adnan A. Tahir; Yiyuan Shen; Jinyue Wei; Kunpeng Wu; Muhammad Saifullah (Global and Planetary Change, 2025)

Advancements in photobioreactor systems: Optimizing operations for enhanced microalgal growth and bioremediation - Zubair Hashmi; Ibrahim Maina idriss; Juliana Zaini; Muhammad Saifullah Abu Bakar; Muhammad Roil Bilad (Algal Research, 2025)

Exploring the propagation characteristics from meteorological to hydrological drought across diverse climate regions in the upper Indus Basin, Pakistan - Arif Hussain; Jianxia Chang; Azfar Hussain; Zhou Kai; Guibin Yang; Muhammad Saifullah (Natural Hazards, 2025)

Dual-layer flat sheet membrane from waste cellulose acetate for natural organic matter removal from surface water - Ibrahima Maina Idriss; Zubair Hashmi; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Yusuf Wibisono; Muhammad Roil Bilad (Journal of Water Process Engineering, 2025)

Seasonal Variations in Potable Water Quality of Bahawalpur City: A Comprehensive Assessment of Major Ions, Organic Matter, and Disinfection Byproducts - Sundas Kali; Mazhar Iqbal Zafar; Abida Farooqi; Muhammad Saifullah; Sajida Rasheed; Muhammad Bilal khan Niazi; Amir Waseem; Luiza C. Campos (Environmental Monitoring and Assessment, 2025)

Biochars Induced Changes in CO2 Evolution and Biochemical Properties of an Alkaline Subtropical soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq; Choudhary Muhammad Saqlain (Journal of Soil Science and Plant Nutrition, 2025)

A Novel Optimized Vibration-based Energy Harvester for Leak Detection in Wall-mounted Water Pipelines - Muhammad Faizan Mysorewala; Mati-Ur-Rasool Ashraf Virk; Mujahid Naqeebuddin Syed; Abdul-Wahid Saif; Lahouari Cheded; Saifullah Shafiq; Karim Sattar (Water Resources Management, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Effects of light color on growth, nutrient uptake, and harvesting of the indigenous strain of Chlorococcum sp. - Zubair Hashmi; Juliana Zaini; Rosnah Abdullah; Muhammad Saifullah Abu Bakar; Muhammad Roil Bilad (Bioresource Technology Reports, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Novel polynomial Abet data augmentation algorithm with GRU paradigm for nuclear power prediction - Saifullah Khan; Saeed Ehsan Awan; Yasir Muhammad; Ihtesham Jadoon; Muhammad Asif Zahoor Raja (Annals of Nuclear Energy, 2024)

Improving canopy transpiration model performance by considering concurrent hot and dry conditions - Dianyu Chen; Xiaotao Hu; Xingwu Duan; Daxin Yang; Youke Wang; Xing Wang; Muhammad Saifullah (Agricultural Systems, 2024)

Prediction of drought regulating gene (s) in barley (Hordeum vulgare L.) using express sequence tags (ESTs) through in silico approaches - Muhammad Naveed Shahid; Fatima Maqbool; Saifullah (South African Journal of Botany, 2024)

A novel cloud enabled smart carbon neutral hydroponic setup for stem cutting propagation of tropical tree species - Navod Neranjan; Ahmad Muzakker Khalid; Zakwan Zakaria; Faizah Metali; Muhammad Saifullah Abu Bakar; Hayati Yassin (Computers and Electronics in Agriculture, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Waste cellulose acetate-based dynamic membrane for NOM-containing river water filtration - Ibrahim Maina Idriss; Nurul Fadillah; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Wahyunanto Agung Nugroho; Yusuf Wibisono; Asep Bayu Dani Nandiyanto; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2024)

Spatiotemporal variability of precipitation concentration in Pakistan - Muhammad Zaman; Muhammad Adnan Shahid; Ijaz Ahmad; Yan‐Jun Shen; Muhammad Usman; Muhammad Imran Khan; Muhammad Saifullah (International Journal of Climatology, 2023)
Precipitation is a meteorological variable that plays a vital role in determining water resources and managing water risks. The intensity and frequency of precipitation extremes have increased in recent years; however, the changes in precipitation regimes across Pakistan remain unclear. This study analysed spatial and temporal changes in the precipitation concentration index (PCI) and concentration index (CI) from 100 meteorological stations across Pakistan from 1981 to 2017. Using innovative trend analysis (ITA) and Pettitt's test, we detected trends and change points in the annual and wet season PCI and CI. Additionally, we examined the relationship between PCI/CI values and latitude and altitude. The results revealed that the CI and PCI ranged between 0.48–0.78 and 10–55, respectively, with higher values being more prevalent in the dry and hot zones of the country. The study established a linear relationship between PCI/CI values, latitude and altitude, with higher values at lower altitudes and a decrease in values from south to north. Most stations presented a significant positive ITA trend for PCI and CI from 1981 to 2017, with a change between 1985 and 1995, indicating an overall increase in heavy precipitation events in the area. These findings are crucial for disaster preparedness, water resource planning, the mitigation of drought and flood risks, and conservation efforts.

Incorporating dynamic schemes of canopy light extinction coefficient improves transpiration model performance for fruit plantations - Dianyu Chen; Xiaotao Hu; Xingwu Duan; Xinguang Wei; La Zhuo; Xing Wang; Jing Guo; Saifullah Muhammad (Journal of Hydrology, 2023)

Challenges, limitations, and applications of nanofluids in solar thermal collectors—a comprehensive review - Lukman Ahmed Omeiza; Muhammad Abid; Yathavan Subramanian; Anitha Dhanasekaran; Saifullah Abu Bakar; Abul Kalam Azad (Environmental Science and Pollution Research, 2023)

Exploring the Intertwined Nexus between Globalization, Energy Usage, Economic Complexity, and Environmental Quality in Emerging Asian Economies: A Pathway Towards a Greener Future - Muhmmad Asim Rafiq; Abdul Rauf; Saifullah Shakir; Ameer Muhammad Aamir Abbas; Huaping Sun; Saira Abid (Environmental Science and Pollution Research, 2023)

Prediction of land use and land cover changes (LULC) and urban growth analysis in Dhaka Metropolitan Area (DMA) using CA-Markov model and geospatial techniques - Md. Kausar Hossein; Azom Ahmed; Muhammad Jasim Uddin; A.S.M. Saifullah; Md. Abu Hamjalal Babu; Tasrin Sarker (Arabian Journal of Geosciences, 2023)

Unearthing research trends in emissions and sustainable development: Potential implications for future directions - Khalid Mehmood; Saifullah; Xuchun Qiu; Muhammad Mohsin Abrar (Gondwana Research, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Knowledge, attitude, and perceptions about cancer genetic testing in clinical practice in Karachi, Pakistan - Shameel Shafqat; Masooma Naseem; Masooma Rana; Zehra Naseem; Warda Ahmed; Muhammad Daniyal Musharraf; Arisha Zaheer; Ahmed Safiullah Shaikh; Muhammad Bazil Musharraf; Mahnoor Niaz; Saifullah Khan; Rabiya Irfan; et al. (Journal of Community Genetics, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Macroalgae for biomonitoring of trace elements in relation to environmental parameters and seasonality in a sub-tropical mangrove estuary - Mir Talas Mahammad Diganta; A.S.M. Saifullah; Md. Abu Bakar Siddique; Mohammad Mostafa; Md. Shemul Sheikh; Muhammad Jasim Uddin (Journal of Contaminant Hydrology, 2023)

Modelling of geomorphological features of fluvial systems in Eromanga Basin and North Sea using 3D seismic attributes - Haris Ahmed Khan; Saifullah Abdul Qadir; Muhammad Jahangir Khan; Faraz Hasan Siddiqui; Mirza Saad Ahsan (Journal of Earth System Science, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Impact of Water Regimes on Minimizing the Accumulation of Arsenic in Rice (Oryza sativa L.) - Muhammad Tahir Shehzad; Muhammad Sabir; Saifullah; Abu Bakkar Siddique; Mohammad Mahmudur Rahman; Ravi Naidu (Water, Air, & Soil Pollution, 2022)

Temperature-Dependent Speciation Analysis of Chromium Immobilized in Calcium Hydroxyapatite Matrix - Sajid Iqbal; Yasir Faiz; Messaoud Harfouche; Muhammad Saifullah; Jong-Il Yun (International Journal of Environmental Research, 2022)

The impact of COVID-19 pandemic on air pollution: a global research framework, challenges, and future perspectives - Khalid Mehmood; Sana Mushtaq; Yansong Bao; Saifullah; Sadia Bibi; Muhammad Yaseen; Muhammad Ajmal Khan; Muhammad Mohsin Abrar; Zaid Ulhassan; Shah Fahad; George P. Petropoulos (Environmental Science and Pollution Research, 2022)

Pollution characteristics and human health risk assessments of toxic metals and particle pollutants via soil and air using geoinformation in urbanized city of Pakistan - Khalid Mehmood; Yansong Bao; Roman Abbas; Saifullah; George P. Petropoulos; Hamaad Raza Ahmad; Muhammad Mohsin Abrar; Adnan Mustafa; Alwaseela Abdalla; Katia Lasaridi; Shah Fahad (Environmental Science and Pollution Research, 2021)

Prediction of changes in water balance of Nam Co Lake under projected climate change scenarios - Muhammad Adnan; Shichang Kang; Muhammad Saifullah; Shiyin Liu; Guoshuai Zhang; Qiudong Zhao; Muhammad Abrar Faiz; Muhammad Zaman (Hydrological Sciences Journal, 2021)

Nutrient Availability to Maize Crop (Zea mays L.) in Biochar Amended Alkaline Subtropical Soil - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Muhammad Ashfaq (Journal of Soil Science and Plant Nutrition, 2021)

Carbon-Based Slow-Release Fertilizers for Efficient Nutrient Management: Synthesis, Applications, and Future Research Needs - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Mohammad I. Alwabel; Rifat Hayat; Muhammad Akmal; Shahzada Sohail Ijaz; Sarosh Alvi; Obaid-ur-Rehman (Journal of Soil Science and Plant Nutrition, 2021)

Soil nutrient status and crop productivity after 6 years of conservation tillage in a subtropical dryland - Sana ur Rehman; Shahzada Sohail Ijaz; Khalid Saifullah Khan; Muhammad Ansar; Qaiser Hussain (Arabian Journal of Geosciences, 2021)

Identification of irrigation potential areas, using multi-criteria analysis in Khyber District, Pakistan - Muhammad Waleed; Sajid Rashid Ahmad; Muhammad Asif Javed; Saifullah Samiullah (Environmental Science and Pollution Research, 2020)

Chemical fractionation and risk assessment of trace elements in sewage sludge generated from various states of Pakistan - Umair Riaz; Ghulam Murtaza; Saifullah; Muhammad Farooq; Humera Aziz; Ayesha Abdul Qadir; Shahzada Munawar Mehdi; Muhammad Akram Qazi (Environmental Science and Pollution Research, 2020)

Feedstock-induced changes in composition and stability of biochar derived from different agricultural wastes - Tayyba Kanwal Choudhary; Khalid Saifullah Khan; Qaiser Hussain; Munir Ahmad; Muhammad Ashfaq (Arabian Journal of Geosciences, 2019)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Carbon mineralization in subtropical dryland soil amended with different biochar sources - Sehar Sultan; Khalid Saifullah Khan; Muhammad Akmal; Zammurad Iqbal Ahmed; Qaiser Hussain; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Response of soil microbial biomass and enzymatic activity to biochar amendment in the organic carbon deficient arid soil: a 2-year field study - Muhammad Irfan; Qaiser Hussain; Khalid Saifullah Khan; Muhammad Akmal; Shahzada Sohail Ijaz; Rifat Hayat; Azeem Khalid; Muhammad Azeem; Muhammad Rashid (Arabian Journal of Geosciences, 2019)

Strategic use of water: a step toward cadmium-free basmati rice (Oryza sativa L.) - Muhammad Naveed; Saifullah; Umair Riaz; Ghulam Murtaza; Sadia Bibi; Ammara Arooj; Qamar uz Zaman (Paddy and Water Environment, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Poverty within watershed and environmentally protected areas: the case of the indigenous community in Peninsular Malaysia - Fatimah Binti Kari; Muhammad Mehedi Masud; Siti Rohani Binti Yahaya; Md. Khaled Saifullah (Environmental Monitoring and Assessment, 2016)

Organic amendments differ in their effect on microbial biomass and activity and on P pools in alkaline soils - Muhammad Asghar Malik; Khalid Saifullah Khan; Petra Marschner; Safdar Ali (Biology and Fertility of Soils, 2013)